2005
DOI: 10.2307/3583408
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Community-Based Distribution Programmes on Contraceptive Uptake in Resource-Poor Settings: Evidence from Ethiopia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Findings of studies on other community-based health programs in other countries also support this study. Studies on the effect of community-based reproductive health communication interventions on contraceptive use among young married couples in Bihar, India, and community-based distribution programs on contraceptive uptake in Ethiopia have indicated that demand for contraception increases in intervention areas 9,10…”
Section: Discussionmentioning
confidence: 99%
“…Findings of studies on other community-based health programs in other countries also support this study. Studies on the effect of community-based reproductive health communication interventions on contraceptive use among young married couples in Bihar, India, and community-based distribution programs on contraceptive uptake in Ethiopia have indicated that demand for contraception increases in intervention areas 9,10…”
Section: Discussionmentioning
confidence: 99%
“…After adopting the National Population Policy of Ethiopia and developing a clearly stated family planning programme following the change of government in 1991, international family planning service-providing and funding organisations such as the Packard Foundation Ethiopia, Marie Stopes International -Ethiopia, the German Development Agency and others have engaged in supporting and implementing the family planning programme of Ethiopia (Ahmed & Mengistu, 2001). A number of local non-government organisations (NGOs) were also organised under the umbrella of the Ethiopian Consortium of Reproductive Health Associations (CORHRA) -the then Consortium for Family Planning NGOs in Ethiopia (Tawye, Jotie, Shigu, Ngom & Maggwa, 2005). To expand and improve the services, a community-based distribution (CBD) programme was later introduced by local as well as international NGOs with the material and financial support of donors and development partners (Ahmed & Mengistu, 2002).…”
Section: The Family Planning Programme In Ethiopiamentioning
confidence: 99%
“…The factors responsible for such varied picture operate at the individual, family and community level with their roots in the socio-economic and cultural milieu of Indian Society. Recent evidence from Ethiopia, where the majority of the population live in rural areas, indicates that the country's contraceptive prevalence rate could double if the current community based reproductive health program were expanded to include provision of family planning 9 . Hence, the present study was designed to find out the contraceptive prevalence and identify the different variables which affect the contraceptive prevalence among the urban slum community in Mumbai.…”
Section: Introductionmentioning
confidence: 99%